The comparison of two approach of exercise training and therapeutic on some structural changes in testicular tissue in rats with ADHD - Mohammadjavad Arab; Hasn Abdi (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2019)
Aim and Background: Some studies have looked at the effects of drugs such as methylphenidate on sexual parameters, testicular development, sperm motility and spermatogenesis, and the negative effects of these drugs have been shown on this variable. Therefore, the purpose of this study was the comparison of two approach of exercise training and therapeutic on some structural changes in testicular tissue in rats with Attention Deficit-Hyperactivity Disorder (ADHD).